Analisis Penggunaan Sarana Sistem Pembuangan Air Limbah di Rumah Penduduk Desa Terusan Kabupaten OKU Tahun 2021 - Ansori; Akhmad Dwiprayetno; Chairil Zaman (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
The problem of environmental health is one of the problems that needs to be prioritized. Land ownership is to find out the criteria for the house to meet the requirements of a healthy house including knowing whether it has available land to allow it to build a simple sewerage channel, to build a simple sewerage channel and the level of community income and community knowledge, and whether or not it is able to construct a simple sewerage. This study uses a Cross Sectional design to determine environmental factors related to SPAL ownership. The population of this study was all KK in the village of Canal in the working area of ??UPTD Puskesmas Sekar Jaya and the sample of this study was 191 samples. Data were analyzed using Chi-Square statistical test. From the results of the study, it was found that the frequency distribution of respondents who have SPAL ownership available is 39.3%, while those who are not available are 60.7%, in the category of land availability there are 36.6% and no 63.4%, good knowledge 77.0% , and not good 23.0%, high income 35.6% and low income 64.4%. The conclusion of this study is that there is a significant relationship between land availability and SPAL ownership with a P-Value of 0.001 , there is no significant relationship between knowledge and ownership of SPAL with a P-Value of 0.008 , there is a significant relationship between income and SPAL ownership with a P-Value of 0.000.